Legal expenses in the Code of Criminal Procedure - Dicu, Oana-Alina (Technium Social Sciences Journal, 2023)
The expenses advanced by the state and those incurred by the parties in the conduct of criminal proceedings are called court expenses and are divided into the expenses incurred in criminal proceedings until they are completed – including those related to appeals, among which we mention ordinary and extraordinary ones. State authorities incur expenses for spaces where prosecutor's offices and courts operate, including remuneration of senior and judicial officials, which are within the competence of the state as judicial power. Also, the courts, when organizing criminal trials, getting to administer the evidence, ordering the evidentiary procedures and establishing to what extent the defendant committed the crime, determining the amounts owed by the Public Ministry or by the party responsible for conducting the criminal proceedings. As a result, all the expenses mentioned sometimes end up being very high for all parties involved in the criminal proceedings, as appropriate. According to Article 272, paragraph 1, the above-mentioned expenses will be covered by the responsible party, according to the law, or will be advanced by the State, while Articles 274-275 of the Code of Criminal Procedure clarify precisely which part of the criminal proceedings will cover certain expenses. At first glance, we notice that a large part of Romanian citizens find it difficult to understand the difference between legal costs and court costs. The novelty arises from the fact that this topic is approached from such a succinct perspective that there are situations in which phrases such as legal costs and court costs are often confused.